Acoustic Shell Optimization in Opera Houses for Concert Halls - Umberto Derme; Silvana Sukaj; Amelia Trematerra (Applied Sciences)
Opera houses are often used as concert halls with the use of a temporary acoustic shell set on stage. In most cases, the shell shape and its position in the fly tower are decided by theatre technicians, after evaluating the concert programme and considering the conductor and the musicians’ requests, without being supported by an acoustic analysis. This paper describes the acoustic shell influence on the acoustic field of a baroque theatre when changing its dimensions and the orchestra staff, with and without the choir, when the theatre is used as a concert hall. The “Opera di Roma” case study is presented, and the main acoustic parameters’ trends and their sensitivity are analyzed. The shell layout optimization, which is suggested in the prediction analysis of the case study, does not coincide with the ones preferred by the musicians. The main reasons for this controversial result are explained in the paper, underlining the rules determining the musicians’ opinions during the acoustic design and/or analysis process, to better focalize the applied acoustics activities.